1998
DOI: 10.1021/jf970670x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microwave Heating on the Loss of Vitamin B12 in Foods

Abstract: To clarify the effects of microwave heating on the loss of vitamin B(12) in foods, raw beef, pork, and milk were treated by microwave heating and then their vitamin B(12) contents were determined according to a chemiluminescent vitamin B(12) assay with hog intrinsic factor. Appreciable loss ( approximately 30-40%) of vitamin B(12) occurred in the foods during microwave heating due to the degradation of vitamin B(12) molecule by microwave heating. When hydroxo vitamin B(12), which predominates in foods, was tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 11 publications
2
45
0
Order By: Relevance
“…Our previous studies have demonstrated that appreciable loss (~40%) of B 12 occurs in certain foods during microwave heating (9). Prolonged heat-treatments (boiling for 30 min or microwaving for 6 min) of authentic OH-B12 solution have demonstrated the accelerated formation of B12 degradation products, some of which are identified as the compounds with various changes to lower-ligand moiety (cobalt-coordinated nucleotide) (9,17).…”
Section: Effects Of Various Cooking Methods On B12 Contents Of the Ramentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have demonstrated that appreciable loss (~40%) of B 12 occurs in certain foods during microwave heating (9). Prolonged heat-treatments (boiling for 30 min or microwaving for 6 min) of authentic OH-B12 solution have demonstrated the accelerated formation of B12 degradation products, some of which are identified as the compounds with various changes to lower-ligand moiety (cobalt-coordinated nucleotide) (9,17).…”
Section: Effects Of Various Cooking Methods On B12 Contents Of the Ramentioning
confidence: 99%
“…Our previous studies have demonstrated that loss of B 12 significantly occurs in beef, pork, and milk during microwave heating ( 9 ). Although the effects of various cooking methods on the proximate composition, mineral, and vitamin (A, E, B 1 , naiacin, and B 6 ) contents of certain fish fillets have been investigated ( 10 ), it is still unclear how much B 12 is lost in raw fish meats during cooking; the lack of this information may be due to the difficulty of B 12 assay in foods.…”
mentioning
confidence: 97%
“…This might be due to an increased prevalence of atrophic gastritis (Streeter et al, 1976;Ihamäki et al, 1979;Krasinski et al, 1986;Carmel et al, 1987;Jones et al, 1987) and certain medicaments (Adams et al, 1983;Belaiche et al, 1983;Kittang & Schjönsby, 1987;Lindstedt, 1999). The extent of vitamin B 12 malnutrition in the elderly is unknown but concern relates to the observation that microwave heating of food can cause degradation of hydroxo-cobalamin (Watanabe et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…As many as 33 subjects amongst non vegetarian group, were eating such nonveg diet only on occasional basis. Further, some traditional ways of cooking, may be responsible for partial degradation of vitamin B12 [9].…”
Section: Discussionmentioning
confidence: 99%